EVALUATION OF ALCOHOLIC DRINK PROHIBITION POLICY IN SUKABUMI CITY 2022 - Sulaiman Mikha Hermanto; M. Rijal Amirulloh; Dine Meigawati (DIA: Jurnal Administrasi Publik, 2023)
The purpose of this research is to find out about the evaluation of the ban on alcoholic beverages in Sukabumi City in 2022. The method used in this study is a qualitative method with a case study approach. The techniques used in collecting data include observation, interviews, documentation, audio-visual material. The results of the study indicate that the policy objectives have been achieved but there are still those who violate them so that the policy objectives have not been achieved, there are obstacles in the implementation of the prohibition of alcoholic beverages, the implementation has not been responded to as a whole so that the involvement of all parties is needed, lack of budget and vehicle infrastructure for related agencies,